Correlation between Central Memory T Cell Expression and Proinflammatory Cytokine Production with Clinical Presentation of Multibacillary Leprosy Relapse: e0127416 - Esquenazi, Danuza; Alvim, Iris MariaPeixoto; Pinheiro, Roberta Olmo; Oliveira, Eliane Barbosade; Moreira, Lilian deOliveira; Sarno, Euzenir Nunes; Nery, Augusto daCosta (PloS one, 2015)
Background Despite the efficacy of multidrug therapy, surviving Mycobacterium leprae causes relapse in some leprosy patients, and these patients present signs and symptoms of disease after healing. This study focused on the cellular immune response in relapsed multibacillary patients but also included non-relapsed multibacillary cured individuals, newly diagnosed and untreated multibacillary patients, paucibacillary patients just before the beginning of treatment, and voluntary healthy individuals for comparative analysis. Methodology/Principal Findings Inhibition of CD86 expression in the blood-derived monocytes and dendritic cells of relapsed multibacillary patients, either ex vivo or after M. leprae antigen stimulation was observed by flow cytometry. In addition, no significant changes in Interferon-gamma (IFN-g) expression were observed in 5-day culture supernatants of relapsed patients in response to M. leprae, neither before nor after treatment, as measured by ELISA. However, these patients demonstrated a significant increase in central memory CD4+ and CD8+ M. leprae-specific T cells, as assessed by multiparametric flow cytometry. The increase in frequency of central memory T cells in relapsed patients strongly correlated with the bacillary index and the number of skin lesions observed in these subjects. Moreover, cytokine multiplex analysis demonstrated significant antigen-specific production of Interlukin-1beta (IL-1b), IL-6, and Tumour Necrosis Factor (TNF) in the relapsed group with extremely low IL-10 production, which resulted in a high TNF/IL-10 ratio. Conclusions/Significance Inhibition of CD86 expression may function to reduce effector T cell responses against the M. leprae antigen. Furthermore, the predominance of central memory T cells in association with the high TNF/IL-10 ratio and no observed IFN-g production may be related to the pathogenesis of relapse in multibacillary leprosy. Therefore, our findings may be a direct result of the clinical presentation, including a number of skin lesions and bacterial load, of relapsed patients. To our knowledge, this is the first study correlating immune response parameters with the clinical presentation of relapsed multibacillary patients.